Development of fuzzy logic controller for improving the performance of ward leonard speed system / Raymond Ngang - Ngang, Raymond (1997)
This project concerns about developing a fuzzy logic controller for a Ward Leonard speed control system. Many engineers have tried to use conventional PID (Proportional Integral Derivative) controller to control this system previously, but not successful because the control task is non-linear. First part of this paper will cover the basic knowledge of fuzzy logic sets followed by translating the crisp data into linguistic variables under fuzzification section. The defuzzification is to change back the linguistic variables result into a real value that represent the power setting of the motor in kilowatts. The discussion is limited only to the development of software. The hardware part is discussed in another part of this entire project. Because of limited time, the hardware part was not completed. Only the software part is completed which involves the cross debugging between C-language code and the fuzzy software tools.